Policy rules and the inflation surge: The case of the ECB - Balint Tatar; Volker Wieland (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2024)
This paper investigates the implications of monetary policy rules during the surge and subsequent decline of inflation in the euro area and compares them to the interest rate decisions of the European Central Bank (ECB). It focuses on versions of the Taylor (1993) and Orphanides and Wieland (OW) (2013) rules. Rules that respond to recent outcomes of HICP Core or domestic inflation data called for raising interest rates in 2021 and well ahead of the rate increases implemented by the ECB. Thus, such simple outcome-based policy rules deserve more attention in the ECB's monetary policy strategy. Interestingly, the rules support the recent shift of the ECB to policy easing. Yet, they add a note of caution by suggesting that policy rates should not decline as fast as apparently anticipated by traded derivative-based interest rate forecasts.
Keywords: E42; E43; E52; 330; Monetary policy; interest rates; European Central Bank; Taylor rule; OrphanidesWieland rule; New Keynesian macro-epidemic models